Trajectory of changes in myelin basic protein levels in cerebrospinal fluid during ageing and its association with biomarkers of Alzheimer’s disease - Man-Yu Xu; Xu Yi; Shan Huang; Qing-Hua Wang; Yu-Jie Lai; Zhen Wang; Dong-Yu Fan; Gui-Hua Zeng; Yu-Di Bai; Ying-Ying Shen; Fan Zeng; Qing-Xiang Mao; et al. (Translational Psychiatry)
Abstract Myelin loss has been implicated in the development of Alzheimer’s disease (AD). We investigated the changes in myelin basic protein (MBP) levels in cerebrospinal fluid (CSF) in an ageing cohort comprising 116 cognitively normal and Aβ-negative controls aged 26 to 82 years, as well as in a clinical cohort. We found that CSF MBP levels was positively correlated with age in a nonlinear pattern over the lifetime of the ageing cohort and that CSF MBP continually increased until it began to decline around age of 51 years and rose again around age 62. CSF MBP levels were correlated with the Mini-Mental State Examination (MMSE) score and CSF phosphorylated tau-181 (p-tau181) and total tau (t-tau) levels but not the Aβ42/Aβ40 ratio. CSF MBP levels moderated age-related changes in cognitive function. In the clinical cohort, CSF MBP levels were higher in the CSF Aβ+ patients than in the CSF Aβ- participants, and CSF MBP levels were higher in the Aβ–PET+ patients than in the Aβ–PET- participants. CSF MBP levels were higher in apolipoprotein E ε4 allele (APOE-ε4) carriers than in APOE-ε4 noncarriers in the clinical cohort. Our study reveals the possible changes in CSF MBP levels during ageing and in AD patients, providing evidence that demyelination is involved in brain ageing and AD pathogenesis in humans.